Direct cost and socio-demographic factors associated with alcohol consumption among Tema adult residents in Ghana: a quantitative study. (2nd January 2022) - Frimpong-Mansoh, Rita Patricia; Amon, Samuel; Agyemang, Samuel Agyei; Sackey, Samuel; Aikins, Moses
ABSTRACT: Background: Despite the numerous health and social problems associated with alcohol use, its use is increasing in many African countries. This study assessed the direct cost and socio-demographic factors associated with alcohol use among adults in a coastal commercial community in Ghana. Methods: A cross-sectional survey of 412 adults was undertaken. Data were collected using adapted questions from validated standard tools. Logistic regression analysis was used to determine the association between alcohol use and socio-demographic factors. Kruskal-Wallis and Wilcoxon Rank Sum tests were used to determine statistical significance in mean cost differences of alcohol use. Results: Averagely, participants spent US5.06 daily on alcohol. Most men (39.3%) and women (44.6%) consume beer more than other alcoholic beverages. Men were more likely to consume alcohol compared to women. Also, people with no formal education and those with tertiary education have equal likelihood of consuming alcohol. Alcohol use among people with higher monthly income was 1.72 (95% CI:0.94–3.15) times higher compared to those with lower income. Conclusion: The cost of alcohol use varies among men and women. Socio-demographic factors influence alcohol use. Hence, public health intervention to reduce alcohol use in these communities should take cognizance of these factors.